Конкурс як елемент юридичного складу підстави виникнення трудових відносин з науковцями - Яковлєва, Г. О. (право, 2016)
The article is devoted to the procedure of competitive selection of scientific staff. The author emphasizes the gaps in legislation on the competition for researchers’ vacancies in the research institutions. The article also analyzes the requirements for candidates for researchers and examines the procedure of the invalid competition’s results determining. // Стаття присвячена процедурі конкурсного відбору наукового персоналу. Автор підкреслює прогалини у законодавстві змагань щодо вакансій дослідників у дослідницьких установах. У статті також аналізується вимоги до кандидатів для дослідників та вивчає процедуру визначення недійсних результатів конкуренції.
Competition as an element of legal structure of the ground of the arising of labour relations with scientists
Keywords: competition; researcher; vacancies; research institution; academic (scientific, scientific and technical, technical) council; конкуренція; дослідник; вакансія; науково-дослідна установа; академічна (наукова, науково-технічна, технічна) рада